2009
DOI: 10.1111/j.1944-9720.2009.01037.x
|View full text |Cite
|
Sign up to set email alerts
|

One Right Way, Intercultural Participation, and Language Learning Anxiety: A Qualitative Analysis of Adult Online Heritage and Nonheritage Language Learners

Abstract: This study investigated self‐assessed anxious learners who enrolled in online Spanish courses to determine if their anxiety was mediated by the lack of face‐to‐face (F2F) and other synchronous learning interactions. Participants were enrolled in courses at two postsecondary institutions located in south‐central Texas. Narrative analysis was used to interpret the interview data. Findings indicated participants experienced language anxiety because their previous F2F and online learning experiences enforced the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
35
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 51 publications
5
35
0
2
Order By: Relevance
“…A slow but growing appearance of related studies in the past few years indicates that the interest in understanding the interplay between learner and environment with a dynamic/complexity orientation is growing. Promisingly, these researchers have explored contexts (e.g., online environments; Coryell & Clark, ) and learner populations (e.g., dyslexic learners; Csizér et al, ) outside of the traditions and contexts that this review has identified. Even when these texts have been situated outside of the scholarly discourse, they have provided dynamic views of learner attitudes, perceptions, and beliefs, as in the book Language Crossings: Negotiating the Self in a Multicultural World (Ogulnick, ), which featured short chapters by individuals sharing their “linguistic autobiographies,” the descriptions of their own language learning experiences in light of the social, cultural, and political contexts in which they occur.…”
Section: The Dynamic/complexity Orientationmentioning
confidence: 99%
“…A slow but growing appearance of related studies in the past few years indicates that the interest in understanding the interplay between learner and environment with a dynamic/complexity orientation is growing. Promisingly, these researchers have explored contexts (e.g., online environments; Coryell & Clark, ) and learner populations (e.g., dyslexic learners; Csizér et al, ) outside of the traditions and contexts that this review has identified. Even when these texts have been situated outside of the scholarly discourse, they have provided dynamic views of learner attitudes, perceptions, and beliefs, as in the book Language Crossings: Negotiating the Self in a Multicultural World (Ogulnick, ), which featured short chapters by individuals sharing their “linguistic autobiographies,” the descriptions of their own language learning experiences in light of the social, cultural, and political contexts in which they occur.…”
Section: The Dynamic/complexity Orientationmentioning
confidence: 99%
“…The other reason is that students may experience negative emotions when they are assigned to answer questions in synchronous learning environments (Coryell & Clark, 2009;Yang, 2011), and this is especially true of Chinese students (J.-K. Chen & Wei, 2011;Laurence Lwo & Yuan, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the instructor should be responsive with regard to offering live lectures and initiating questions intended to enable discussion, particularly in Chinese culture, where students rely on teachers to fire questions at them (Levinsohn, 2007). However, previous research (C. M. Chen & Lee, 2011;Coryell & Clark, 2009;Yang, 2011) has suggested that students may experience negative emotions when they are assigned to answer questions in synchronous learning environments. For example, students at low cognitive levels may resist answering such questions, because they need more time to think and reflect on the questions (Yang, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Different authors (Casado & Dereshiwsky, 2001;Coryell & Clark, 2009;Kostić-Bobanović, 2009;Liu, 2006;Liu & Jackson, 2008;MacIntyre & Gardner, 1994a, 1994bTallon, 2009;von Wörde, 2003) conclude this phenomenon is a tangible reality for English as a foreign language (EFL) students at the high-school and university levels.…”
Section: Antecedentsmentioning
confidence: 99%